Fibroblast growth factor-2-mediated protection of cardiomyocytes from the toxic effects of doxorubicin requires the mTOR/Nrf-2/HO-1 pathway - Koleini, Navid (Oncotarget, 2017)
BACKGROUND: Cardiotoxic side effects impose limits to the use of anti-tumour chemotherapeutic drugs such as doxorubicin (Dox). There is a need for cardioprotective strategies to prevent the multiple deleterious effects of Dox. Here, we examined the ability of administered fibroblast growth factor-2 (FGF-2), a cardioprotective protein that is synthesized as high and low molecular weight (Hi-, Lo-FGF-2) isoforms, to prevent Dox-induced: oxidative stress; cell death; lysosome dysregulation; and inactivation of potent endogenous protective pathways, such as the anti-oxidant/detoxification nuclear factor erythroid-2-related factor (Nrf-2), heme oxygenase-1 (HO-1) axis. METHODS AND RESULTS: Brief pre-incubation of neonatal rat cardiomyocyte cultures with either Hi- or Lo-FGF-2 reduced the Dox-induced: oxidative stress; apoptotic/necrotic cell death; lysosomal dysregulation; decrease in active mammalian target of Rapamycin (mTOR). FGF-2 isoforms prevented the Dox-induced downregulation of Nrf-2, and promoted robust increases in the Nrf-2-downstream targets including the cardioprotective protein HO-1, and p62/SQSTM1, a multifunctional scaffold protein involved in autophagy. Chloroquine, an autophagic flux inhibitor, caused a further increase in p62/SQSTM1, indicating intact autophagic flux in the FGF-2-treated groups. A selective inhibitor for HO-1, Tin-Protoporphyrin, prevented the FGF-2 protection against cell death. The mTOR inhibitor Rapamycin prevented FGF-2 protection, and blocked the FGF-2 effects on Nrf-2, HO-1 and p62/SQSTM1. CONCLUSIONS: In an acute setting Hi- or Lo-FGF-2 protect cardiomyocytes against multiple Dox-induced deleterious effects, by a mechanism dependent on preservation of mTOR activity, Nrf-2 levels, and the upregulation of HO-1. Preservation/activation of endogenous anti-oxidant/detoxification defences by FGF-2 is a desirable property in the setting of Dox-cardiotoxicity.